Effects of Work Systems on Employee’s Performance at Mawenzi Regional Referral Hospital in Moshi, Tanzania - JOSHUA, LEAH; Onyancha, Hezron; Amembah, A. Lamu Amos (Community Development Journal, 2025)
This study aimed to assess the effects of work systems on employee performance at Mawenzi Regional Referral Hospital in Moshi, Tanzania. The study was grounded in the Competing Values Framework (CVF), the study employed a convergent research design under mixed method approach, combining quantitative and qualitative approaches. The study population comprised 400 employees, using a Yamane formula (1967) a sample size of 200 healthcare workers (doctors and nurses) selected through stratified random sampling and 5 key management personnel chosen via purposive sampling. Primary data was collected using questionnaires for healthcare workers and interview guide for management. Validity and reliability were ensured through expert evaluation and Cronbach’s Alpha (α = 0.79). Quantitative data was analyzed using descriptive analysis via SPSS version 22, while qualitative data was analyzed through contextual analysis. Ethical considerations, including confidentiality and informed consent, were strictly adhered to. The findings revealed that work systems have moderate effect on employee performance with a total mean score of 3.5, with resource availability, communication efficiency, training adequacy, and procedural clarity emerging as key determinants. The study concluded that optimizing work systems through improved resource allocation, streamlined workflows, and enhanced training can boost employee performance and organizational effectiveness. It is recommended that public hospitals particularly Mawenzi Regional Referral Hospital should take deliberate steps to improve their work systems by addressing critical gaps identified in resource provision. Therefore, improving resource allocation and capacity-building efforts with departmental needs is essential.